STRUGGLING AGAINST STEREOTYPE: A STUDY OF MASCULINITY IN AMERICAN GAY TV SERIES - Rudy Rudy (Universitas Gadjah Mada, 2022)
This study aims to analyze the concept of masculinity in the gay male community and identify the image of masculinity in gay men shown in the American gay television series. Data for this qualitative research was gathered from several American gay TV series in the 2000s. The data analysis process involved representation theory in interpreting the dialogs and the scenes in the television series. The study found that masculinity does not always have to be associated with physical strength and heterosexuality because there are other essential aspects such as the ability to achieve success and to meet the needs of life that can be used to conceptualize masculinity. It also revealed that American gay television series frequently showed the representation of masculinity in gay characters to reject the stereotype through images such as physical strength in sports, attractive physical appearance, profession, and ability to achieve success.